The relationship between intrinsic job perfomance and job motivation among employee in Majlis Bandaraya Melaka Bersejarah / Nurulashikin Mazlee - Mazlee, Nurulashikin (Faculty of Business and Management, 2013)
Majlis Bandaraya Melaka Bersejarah (MBMB) is located at Graha. Makmur, No. 1, Jalan TUN Abdul Razak - Ayer Keroh, Hang Tuah Jaya, 75450 Melaka, Malaysia. In Majlis Bandaraya Melaka Bersejarah (MBMB), there are have 15 departments In this organization which are Department of Engineering, Valuation and Property Management, Department of Management, Department of Licensing and Health, Department of Information Technology, Department of Law and Enforcement,Department of Special Projects and Environment, Department of Finance, Department of City Planning, Department of Corporate Affairs and Public Relations, Department of City Beautification, Building Control Department, Department of Business Management and Customer Premises, Department of Community Infrastructure & Logistics and One Stop Centre (OSe). According to Encik Hafiz bin Haji Hassan (2013), Assistant Manager of Management Deparment in Majlis Bandaraya Melaka Bersejarah has been said when employees doing their task, he has declared that the employees has lack of motivation because of many works to do and tend to high pressure. If not solved, this problem had resulted in the organization's work processes disrupted. So, to solve this problem, the top management has been decided to send their employees for training program to improve motivation level of their employees. Motivation is one of important value in an organization especially in Majlis Bandaraya Melaka Bersejarah to achieve the organization's objective, to reach employee's satisfaction and the most important thing for this organization is to achieve five stars in grading, (Hafiz, 2013). According to Maria (2012), she has been said that by viewed in the context of work, motivation can be defined as the degree of availability of the employees to become involved in their work an to make sustained effort in order to meet some professional objectives, which can be defined individually or organizationally. In this context, motivation can be considered a result of the interdependence between the individual and the organizational context where he or she works, rather than a result of the prevailing individual motivations. Moreover in Majlis Bandaraya Melaka Bersejarah, they believe that success of productivity is dependent on employee commitment, job satisfaction, skills, and motivation. Work motivation is a set of external and internal forces that commence the behavior related to work and establish its direction, form, duration and intensity (Nadia, 2011 ). The definition identifies the effect of the external forces like nature of the work to be performed and reward system of the organization. For innate forces of an individual, the examples like motives and needs of a person on the behaviors related to work. Therefore, the current study attempts to explore the relationship between job lnotivation and job satisfaction among employees in Majlis Bandaraya Melaka Bersejarah.